Associations between intensive diabetes therapy and NMR-determined lipoprotein subclass profiles in type 1 diabetes[S] - Ying Zhang; Alicia J. Jenkins; Arpita Basu; Julie A. Stoner; Maria F. Lopes-Virella; Richard L. Klein; Timothy J. Lyons (Journal of Lipid Research, 2016)
Our objective is to define differences in circulating lipoprotein subclasses between intensive versus conventional management of type 1 diabetes during the randomization phase of the Diabetes Control and Complications Trial (DCCT). NMR-determined lipoprotein subclass profiles (NMR-LSPs), which estimate molar subclass concentrations and mean particle diameters, were determined in 1,294 DCCT subjects after a median of 5 years (interquartile range: 4–6 years) of randomization to intensive or conventional diabetes management. In cross-sectional analyses, we compared standard lipids and NMR-LSPs between treatment groups. Standard total, LDL, and HDL cholesterol levels were similar between randomization groups, while triglyceride levels were lower in the intensively treated group. NMR-LSPs showed that intensive therapy was associated with larger LDL diameter (20.7 vs. 20.6 nm, P = 0.01) and lower levels of small LDL (median: 465 vs. 552 nmol/l, P = 0.007), total IDL/LDL (mean: 1,000 vs. 1,053 nmol/l, P = 0.01), and small HDL (mean: 17.3 vs. 18.6 ¼mol/l, P < 0.0001), the latter accounting for reduced total HDL (mean: 33.8 vs. 34.8 ¼mol/l, P = 0.01). In conclusion, intensive diabetes therapy was associated with potentially favorable changes in LDL and HDL subclasses in sera. Further research will determine whether these changes contribute to the beneficial effects of intensive diabetes management on vascular complications.